#Kitajagakita: the manifestation of modern jewellery design / Mohd Faiz Jalaludin ... [et al.] - Jalaludin, Mohd Faiz; Mohd Sharif, Mohd Hakim; Mohd Hasan, Adib; Muda, Muhammad Shafiq (2021)
As far as the title is concerned, the researcher has developed three objectives. The first objective is to manifest current issues related to the global pandemic COVID-19 into modern jewellery design. The secondary objectives are to fostering awareness of the relationship between subject matter and product design especially jewellery designs and the third objective is to initiate the appreciation initiative towards our frontliners through modern jewellery design. This design research is based on the ideation process that is related directly to the message of appreciation through our frontliners. The ideation begins with developing a figure related to the global pandemic COVID-19. All subject matter was simplified throughout the ideation process and developed into jewellery design. A survey has been carried out to choose the best design as a symbol to show the appreciation towards our frontliners that already risking their lives to protect the citizen from the terror of Coronavirus. The researcher has to produce a jewellery design that synchronized with current issues which are global pandemic COVID- 19. The jewellery design that has been produced is the potential to create awareness about the understanding of subject matter in product design among jewellery consumers. Based on that awareness, it is easier for the consumer to become interested in sophisticated jewellery designs that purposely initiate appreciation towards our frontliners.